A Reconstruction Of Habermas’s Communicative Act In Critical-Normative Arabic Language Epistemology - Rangga Mukti; Muniron Muniron (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2026)
This study reconstructs Jurgen Habermas' theory of communicative action by developing a Critical-Normative Language Epistemology for Arabic language education. Addressing this gap, the study aims to formulate a philosophical framework that integrates communicative rationality with normative orientation in the production and validation of knowledge. Employing a library research design with critical philosophical analysis and conceptual synthesis, the study systematically examines Habermas' communicative action alongside contemporary literature on critical theory, philosophy of language, and Arabic language education. The findings reveal that Habermas' epistemology retains substantial explanatory power but exhibits a normative deficit because communicative validity primarily emphasizes procedural legitimacy rather than the ethical orientation of knowledge. To address this limitation, the study proposes Normative-Transcendental Validity as a meta-validity dimension and formulates the Critical-Normative Language Epistemology (CNLE) Framework, which conceptualizes language as a mechanism for knowledge production, epistemic validation, normative orientation, and emancipatory transformation. The originality of this study lies in reconstructing communicative action into a comprehensive epistemological framework rather than merely reinterpreting it within pedagogical discourse. This framework contributes theoretically to philosophy of science and language epistemology while providing a philosophical foundation for developing Arabic language education that is dialogical, critical, ethically grounded, and emancipatory.